Technical note: Understanding the effect of COVID-19 on particle pollution using a low-cost sensor network. (June 2021) - Chadwick, E.; Le, K.; Pei, Z.; Sayahi, T.; Rapp, C.; Butterfield, A.E.; Kelly, K.E.
Abstract: The 2020 coronavirus pandemic and the following quarantine measures have led to significant changes in daily life worldwide. Preliminary research indicates that air quality has improved in many urban areas as a result of these measures. This study takes a neighborhood-scale approach to quantifying this change in pollution. Using data from a network of citizen-hosted, low-cost particulate matter (PM) sensors, called Air Quality & yoU (AQ&U), we obtained high-spatial resolution measurements compared to the relatively sparse state monitoring stations. We compared monthly average estimated PM2.5 concentrations from February 11 to May 11, 2019 at 71 unique locations in Salt Lake County, UT, USA with the same (71) sensors' measurements during the same timeframe in 2020. A paired t -test showed significant reductions (71.1% and 21.3%) in estimated monthly PM2.5 concentrations from 2019 to 2020 for the periods from March 11-April 10 and April 11-May 10, respectively. The March time period corresponded to the most stringent COVID-19 related restrictions in this region. Significant decreases in PM2.5 were also reported by state monitoring sites during March (p < 0.001 compared to the previous 5-year average). While we observed decreases in PM2.5 concentrations across the valley in 2020, it is important to note that the PM2.5 concentrations did not improve equally in all locations. We observed the greatest reductions at lower elevation, more urbanized areas, likely because of the already low levels of PM2.5 at the higher elevation, more residential areas, which were generally below 2 μg/m 3 in both 2019 and 2020. Although many of measurements during March and April were near or below the estimated detection limit of the low-cost PM sensors and the federal equivalent measurements, every low-cost sensor (51) showed a reduction in PM2.5 concentration in March of 2020 compared to 2019. These results suggest that the air quality improvement seen after March 11, 2020 is due to quarantine measures reducing traffic and decreasing pollutant emissions in the region. Highlights: Significant reductions in PM concentration corresponded to COVID-related restrictions and traffic reductions. Networked low-cost PM measurements identified decreases in PM levels at 50+ locations. The low-cost PM measurements supported findings from sparse state monitors. The greatest percent reductions occurred in locations with the most urban activity.